Overview of sudden cardiac death in young athletes - Sheikh, N.; Sharma, S. (The Physician and Sportsmedicine, 2011)
Sudden cardiac death is the leading cause of nontraumatic mortality in young athletes. The estimated incidence varies; however, recent studies have provided more accurate data. Most cases are attributed to silent hereditary or congenital cardiac disorders, many of which may be detected through preparticipation screening programs. This article provides a comprehensive review of the incidence and etiology of sudden cardiac death in young athletes, with practical advice regarding evaluation and management in light of a large number of recent advances. A brief outline of current perspectives on preparticipation screening programs and prevention is included.